2009
DOI: 10.1016/j.biopsych.2008.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of the Association Between Abandoned Dwellings and Testosterone Level on the Development of Behaviors Leading to Cannabis Use Disorder in Boys

Abstract: Background-The role of testosterone in the development of behaviors presaging cannabis use and subsequently cannabis use disorder was investigated in a prospective study of 208 boys. It was theorized that adverse neighborhood correlates with testosterone level that in turn potentiates behaviors predisposing to cannabis consumption and subsequently diagnosis of cannabis use disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…Increased levels of testosterone at ages 10-12 are predictive of assaultive behavior at ages 12-14, norm-violating behavior at age 16, and cannabis use at age 19 37 . Higher levels of testosterone at age 16 are associated with crime in adulthood 38 .…”
Section: Hormones and Neurotransmittersmentioning
confidence: 99%
“…Increased levels of testosterone at ages 10-12 are predictive of assaultive behavior at ages 12-14, norm-violating behavior at age 16, and cannabis use at age 19 37 . Higher levels of testosterone at age 16 are associated with crime in adulthood 38 .…”
Section: Hormones and Neurotransmittersmentioning
confidence: 99%
“…Abandoned buildings are an acceptable proxy for neighborhood disadvantage and physical disorder and have been found to be potent and salient risk factors for substance use in young adults (Tarter et al, 2009) and premature mortality (Cohen et al, 2003). We are interested in this particular feature of the built-and-social-neighborhood environment because it follows a clear theoretical framework linking neighborhood malaise to crime and incivility and targets a readily quantifi able and malleable feature of the built environment.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…One study found that boys brought up in areas with more boarded-up buildings had higher testosterone levels, and were more risk-taking than boys from similar social groups living in less run down neighbourhoods 26. Higher testosterone is linked with increased aggression, and it makes sense that one might non-consciously become more risk-taking and aggressive when the context feels unsafe.…”
Section: Adaptive Brains and Nervous Systemsmentioning
confidence: 99%